Strategije zmanjševanja telesne mase pri slovenskih judoistih - Kukovica, David (Šport (Ljubljana), 2023)
Body mass is an essential factor in judo as a weight-limited sport. That‘s why competitors regularly use various techniques to quickly reduce body weight in order to compete in the desired weight category. The purpose of the research was to determine the status and use of rapid weight loss practices and the involvement of trainers through a survey questionnaire in Slovenian judokas categorised by Slovenian Olympic Committee. 34 Slovenian categorised judokas with an average age of 19.97 ± 3.02 years participated in the research, who have been practising judo for an average of 12.94 ± 3.94 years. We found that 59% of competitors reduce body weight before competitions. They reduce it in an unplanned and uncontrolled way, as 55% of competitors, on average, start to reduce their body weight by 4.2 ± 0.99 kg only 3-5 days before the competition. Data show that some athletes lose up to 6 kg of body weight before competitions. Competitors reported that coaches rarely get involved in their processes of weight loss reduction. In most cases, coaches do not have oversight or control over the weight loss practices of their trainees. The established situation between judokas and their coaches is worrying since we are discussing categorised athletes at the highest level. The data represent the starting points for updating the training programs for judo coaches and their yearly seminars with additional content regarding the rapid weight loss practices and how to apply them properly.
Keywords: borilni športi; izobraževanje; judo; mladi; šport; telesna masa; trenerji